(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
Archaeological fieldwork at the Etruscan settlement of Forcello (Bagnolo San Vito, Mantova) has been carried out since 1983; excavations led to the discovery of structures and floor levels assigned to nine frequentation phases, dated from 540 to 380-375 BC. This paper offers an overview of the most recent findings, as the Attic ceramic fragments from the aristocratic dwelling called “Casa dei Velna”, whose decoration can be attributed to the Orchard Painter.